CAK NUR PLURALISM: CRITICISM OF THE PHENOMENON RELIGIOUS INTOLERANCE IN INDONESIA - Maku, Hendrikus; Tanggang, Alfian; Maria, Joannes George; Dopo, Julio Pius Zoraida (CV. AFDIFAL MAJU BERKAH, 2024)
This article discusses the phenomenon of religious intolerance in Indonesia through Cak Nur's perspective of pluralism. Pluralism, which is the main framework of this article, is the basis for revealing the complexity of the challenges faced by Indonesian society in understanding and appreciating religious pluralism. Cak Nur, a contemporary Islamic thinker and intellectual, provides a rich perspective on religious diversity and the importance of tolerance in religious dialogue. This article aims to highlight a number of factors that influence the emergence of intolerance in Indonesia. In this article the author uses a qualitative method, namely exploring and studying themes that are relevant to the theme of this article. Even though this country is rich in religious diversity, some groups still experience inequality and there are still tensions between religions. Within the framework of Cak Nur's pluralism, this article presents solutions based on dialogue and education from the perspective of Islamic teachings to overcome misunderstandings about the nature of religious diversity. This analysis also includes the role of social media, especially the Instagram account @jaringangusdurian in shaping public opinion regarding religious tolerance. By understanding Cak Nur's views, this article invites readers to understand and reflect on how Indonesian society can form a shared awareness of the values of pluralism, so that acts of intolerance in the name of religion no longer occur in the archipelago. This article uses Cak Nur's inclusive approach as a key step to reduce tensions and build a solid foundation for religious discourse.